Dimethyl fumarate and extracorporeal photopheresis combination-therapy synergize in inducing specific cell death and long-term remission in cutaneous T cell lymphoma: lymphoma - Şener Gürsoy, Özge Çiçek; Melchers, Susanne; Tengler, Luisa; Beltzig, Paul L.; Albrecht, Jana Dorothea; Tümen, Deniz; Gülow, Karsten; Utikal, Jochen; Goerdt, Sergij; Hein, Tobias; Nicolay, Jan Peter (Leukemia, 2025)
Primary cutaneous T cell lymphomas (CTCL) are characterized by high relapse rates to initially highly effective therapies. Combination therapies have proven beneficial, particularly if they incorporate extracorporeal photopheresis (ECP). The NF-κB inhibitor dimethyl fumarate (DMF) has proven a new, effective drug in CTCL in a clinical phase II study. In vitro experiments with patient-derived SS cells and the CTCL cell lines HH, HuT 78, and SeAx revealed a synergistic effect of DMF and ECP on cell death induction in CTCL cells. Furthermore, an additional increase in the capacity to inhibit NF-κB in CTCL was detected for the combination treatment compared to DMF monotherapy. The same synergistic effects could be measured for ROS production via decreased Thioredoxin reductase activity and glutathione levels. Consequently, a cell death inhibitor screen indicated that the DMF/ECP combination treatment induces a variety of cell death mechanisms in CTCL. As a first step into clinical translation, 4 patients were already treated with the DMF/ECP combination therapy with an overall response rate of 100% and a time to next treatment in skin and blood of up to 57 months. Therefore, our study introduces the combination treatment of DMF and ECP as a highly effective and long-lasting CTCL therapy.
Online veröffentlicht: 23. November 2024
Gesehen am 06.05.2025